FDG PET-CT detection of Unusual Pattern of Metastatic Spread in High-Grade Serous Ovarian Carcinoma (Bangladesh Journal of Nuclear Medicine, 2026)
High-grade serous ovarian carcinoma (HGSOC) is the most aggressive subtype of epithelial ovarian cancer, commonly spreads within the peritoneal cavity through transcoelomic dissemination. Distant metastases, particularly isolated pulmonary involvement without pelvic recurrence, are uncommon. We report a 47-year-old hypertensive and diabetic woman with previously treated high-grade serous carcinoma of the right ovary who underwent total abdominal hysterectomy with bilateral salpingo-oophorectomy, omentectomy, and pelvic lymphadenectomy followed by six cycles of paclitaxel-carboplatin chemotherapy. Post-treatment PET-CT showed no residual disease. After one year of follow-up, imaging revealed multiple pulmonary nodules. Subsequent 18F-FDG PET-CT demonstrated FDG-avid peritoneal deposits consistent with peritoneal seeding, along with pulmonary and pleural metastases and abdominal nodal involvement, without pelvic recurrence. This case highlights an unusual metastatic pattern of HGSOC and underscores the value of FDG PET-CT in detecting occult metastatic disease and assessing disease progression.Bangladesh J. Nuclear Med. 29(1): 88-91, 2026